2021
DOI: 10.1051/0004-6361/202039773
|View full text |Cite
|
Sign up to set email alerts
|

The IBISCO survey

Abstract: We present the analysis of the ALMA CO(2−1) emission line and the underlying 1.2 mm continuum of Mrk 509 with spatial resolution of ∼270 pc. This local Seyfert 1.5 galaxy, optically classified as a spheroid, is known to host an ionised disc, a starburst ring, and ionised gas winds on both nuclear (ultra-fast outflows) and galactic scales. From CO(2−1) we estimate a molecular gas reservoir of MH2 = 1.7 × 109 M⊙, located within a disc of size ∼5.2 kpc, with Mdyn = (2.0 ± 1.1) × 1010 M⊙ inclined at 44 ± 10 deg. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 99 publications
1
3
0
Order By: Relevance
“…The velocities of the putative outflow, therefore, would be significantly smaller than the galaxy escape velocity 10 (∼700 km s −1 at 𝑅 100 pc) and the gas would eventually fall back on the system in a galactic-fountain fashion. Similar results have been found in other studies of individual AGN and starburst systems, which show that the velocities of molecular gas outflows are significantly smaller than the galaxy escape velocity (Zanchettin et al 2021;Fluetsch et al 2019). This includes the iconic starburst M82 (Leroy et al 2015).…”
Section: Implications For the Agn Baryon Cyclesupporting
confidence: 90%
“…The velocities of the putative outflow, therefore, would be significantly smaller than the galaxy escape velocity 10 (∼700 km s −1 at 𝑅 100 pc) and the gas would eventually fall back on the system in a galactic-fountain fashion. Similar results have been found in other studies of individual AGN and starburst systems, which show that the velocities of molecular gas outflows are significantly smaller than the galaxy escape velocity (Zanchettin et al 2021;Fluetsch et al 2019). This includes the iconic starburst M82 (Leroy et al 2015).…”
Section: Implications For the Agn Baryon Cyclesupporting
confidence: 90%
“…However, our estimate of R sc , although consistent with the estimates of the size of the dusty region obtained by two independent methods, is only ∼1.3-1.6R BLR . In general, all other estimates of the size of structures inside the central Mrk 509 parsec obtained independently indicate that R BLR is most likely overestimated, for example, due to the presence of outflows driven by AGN observed for Mrk 509 (e.g., [61]). This reveals the necessity of more intensive homogeneous monitoring in polarized and integral light.…”
Section: Discussionmentioning
confidence: 94%
“…It has been observationally demonstrated that molecular outflows carry more mass than their ionized counterparts, at least in the local universe, and at AGN luminosities below 10 47 erg s −1 (Fiore et al 2017;Fluetsch et al 2021). However, as it happens with the ionized outflow mass rates, the values used to build the molecular gas counterpart of the scaling relations (Cicone et al 2014;Fiore et al 2017) are higher than those found for the general population of quasars (Ramos Almeida et al 2022), ULIRGs (Lamperti et al 2022), and Seyfert galaxies (Alonso-Herrero et al 2019;Domínguez-Fernández et al 2020;Zanchettin et al 2021).…”
Section: A Multiphase View Of Outflowsmentioning
confidence: 99%